Pochodzenie a wiarygodność świadka w rzymskich procesach karnych w świetle wybranych mów Cycerona - Nowicka, Dobromiła (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article is devoted to an analysis of the significance of a witness’ origin to his credibility in the Roman criminal procedure on the basis of selected speeches by Cicero — Pro Fonteio, Pro Scauro and Pro Flacco. The extensive use of arguments relating to the nationality of witnesses testifying against the orator’s clients suggests that such references may have been important in the assessment of the credibility of their testimony, despite the fact that formally Roman law did not introduce any restrictions on testifying based on the witness’ origin. Drawing on her analysis of the selected speeches, the author concludes that the references to a witness’ origin and characteristics attributed to a given nation replace arguments relating to the witness himself, without being of crucial significance on their own and being only a necessity in a situation where there is no information about the witness.
Keywords: testimony; witnesses; Cicero’s speeches; Roman criminal procedure; witness’ origin